Managerial stress and coping - Kumar M., Dileep (LAP Lambert Academic Publishing, 2013)
Today, organizational stress is fetching as a matter of concern to the top management in every organization. Industries, especially financial institutions across the world has witnessed rapid and striking changes at organizational level, that is attributable to economic crisis, globalization, liberalization, increased competition, downsizing, introduction of new technologies, mergers and acquisition etc.Resultant manifestations of these changes are precipitated in the form of acute job stress to both employers as well as employees.Stress affects the human potential in the organization, leads to reduced quality, productivity, health as well as well-being and morale.Even though several studies have been conducted on medical side of stress, there are only a few readings at psycho social level, as far as the banking sector is concerned.This research based book will provide you best of knowledge on occupational stress and coping strategies of employees in banking sector.The objective of this book is to draw attention from the top level decision makers of banking institutions on effective stress management programs.